Implementation of a randomized controlled trial on an inpatient stroke rehabilitation unit: Lessons learned - Lisa Sheehy; Anne Taillon-Hobson; Heidi Sveistrup; Martin Bilodeau; Hillel Finestone (Contemporary Clinical Trials Communications, 2020)
Background/Aims: The objective of this manuscript is to present challenges and solutions that arose during a mid-sized single-site RCT of a rehabilitation intervention performed in an inpatient stroke rehabilitation setting. Methods: Seventy-six participants from an inpatient stroke rehabilitation unit were randomized to experimental and control groups. All participants did 30–45 min of virtual reality (VR) daily for 10–12 sessions. The experimental group did VR targeting sitting balance while the control group did VR with limited arm movement. Challenges during the implementation of the RCT were documented and strategies to mitigate them were applied. Results: Challenges were placed into five categories:1. Recruitment. Our recruitment procedures required multiple steps prior to initiating direct patient contact; one solution would be to have patients consent to be approached about research upon admission to the inpatient unit.2. Patient-specific Issues. Fatigue, pain, vision problems and engagement were managed through scheduling, increasing the workload slowly and personalized modifications to the VR.3./4. Scheduling and Staffing. Recruitment and attendance at VR sessions were maximized through good communication, flexibility and cooperation, between research staff, clinical staff, volunteers, students and participants.5. Technology. Because hospital internet service was poor, a mobile internet data plan was purchased to ensure the system's reliability. Conclusions: We have identified challenges in delivering a rehabilitation intervention on an inpatient stroke rehabilitation unit and some of the measures taken to surmount these challenges. Through good planning, flexibility and collaboration, almost all of the challenges were successfully addressed. Clinical trial registration number: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02285933.